The model of knowledge acquisition in Islam as a foundation for reconstructing the learning paradigm - Hawwa Asy-Syifa; Khaerudin (Mishkat: Journal of Theology and Civilization, 2026)
Studies on knowledge in Islam have extensively discussed epistemology, ethics, and education; however, these aspects have largely been examined separately, leaving the process of knowledge acquisition without a comprehensive conceptual model that can serve as a foundation for learning paradigm reconstruction. This study aims to formulate a Model of Knowledge Acquisition in Islam and examine its relevance as a foundation for reconstructing the learning paradigm. This research employed a qualitative conceptual study by synthesizing the Qur'an, Hadith, classical Islamic scholarship, and academic literature through concept reduction, thematic analysis, and conceptual synthesis. The findings identify five interconnected stages of knowledge acquisition: epistemological foundation, preparation, knowledge acquisition, internalization, and dissemination. The proposed model reconstructs the learning paradigm by shifting its orientation from knowledge transfer toward the formation of knowledgeable, ethical, and practice-oriented individuals. This study contributes to the advancement of Islamic epistemology and philosophy of Islamic education by offering a systematic conceptual model that provides a theoretical foundation for developing holistic Islamic learning. Abstrak Kajian mengenai ilmu dalam Islam telah banyak membahas epistemologi, adab, dan pendidikan. Namun, sebagian besar kajian tersebut masih mengkaji aspek-aspek tersebut secara parsial sehingga belum menghasilkan model konseptual yang menjelaskan proses perolehan ilmu secara utuh sebagai landasan rekonstruksi paradigma pembelajaran. Penelitian ini bertujuan merumuskan Model Proses Perolehan Ilmu dalam Islam serta menganalisis relevansinya sebagai landasan rekonstruksi paradigma pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan jenis kajian konseptual melalui sintesis terhadap Al-Qur'an, hadis, pemikiran ulama, dan literatur ilmiah yang dianalisis menggunakan reduksi konsep, analisis tematik, dan sintesis konseptual. Hasil penelitian menunjukkan bahwa proses perolehan ilmu dalam Islam terdiri atas lima tahapan yang saling terintegrasi, yaitu fondasi epistemologis, persiapan, perolehan ilmu, internalisasi, dan diseminasi. Model yang dihasilkan menjadi landasan konseptual dalam merekonstruksi paradigma pembelajaran dengan menggeser orientasinya dari transfer pengetahuan menuju pembentukan insan yang berilmu, beradab, dan beramal. Penelitian ini berkontribusi memperkaya epistemologi dan filsafat pendidikan Islam melalui penyusunan model konseptual yang sistematis sebagai landasan teoretis bagi pengembangan pembelajaran Islam yang lebih holistik.